THE EFFECT OF PERCEIVED INSTRUCTIONAL EFFECTIVENESS ON STUDENT LOYALTY: A MULTILEVEL STRUCTURAL EQUATION MODEL - Simsek, Guelhayat Goelbasi; Noyan, Fatma (HACETTEPE UNIV, 2009)
Social sciences research often entails the analysis of data with a multilevel structure. An example of multilevel data is containing measurement on university students nested within instructors. This paper concentrate on multilevel analysis of structural equation modeling with educational data. Data used in this study were gathered from 17647 university students in Turkey taking course from 202 instructors during the first term of 2004 academic year. The main topic of this paper is to investigate the effect of Perceived Instructional Effectiveness (PIE) on Student Loyalty (SL). From the both of within and between model results, it was supported that student loyalty is positively affected by perceived instructional effectiveness. The total variation of SL explained by PIE in within model was 57%; on the other hand total variation of SL explained by PIE and instructor's academic status in between model was 92%. The effects of the other background variables were also considered.
Keywords: multilevel structural equation modeling; perceived instructional effectiveness; student loyalty; VALIDITY; Education & Educational Research